Evidence for an estradiol-agonistic action of nebivolol in spontaneously hypertensive rats - Grundt, Christina; Meier, Kirsten; Grundt, Alexander; Lemmer, Björn (Journal of hypertension, 2007)
Objectives: Unlike classical β1-selective blockers, nebivolol (NEB) has vasodilatory properties due to the release of nitric oxide (NO) by a mechanism that is, so far, unknown. We hypothesized that NEB stimulates NO release by binding to estrogen receptors (ER) and subsequent activation of endothelial NO synthase (eNOS). The aim of this study was to elucidate the underlying mechanism of NEB action by investigating estradiol-dependent effects of NEB on the NO system in spontaneously hypertensive rats (SHR). - Methods: The effects of NEB on the NO system were determined by measuring urinary nitrate/nitrite (NOx) as well as eNOS and caveolin-1 protein expression in aortae. - Results: NEB did not influence NOx excretion in sham-operated (SO) female rats during proestrus. In male and ovariectomized female (OVX) rats, NEB increased NOx excretion significantly, whereas NG-nitro-L-arginine methyl ester (L-NAME) inhibited the NEB-induced increase in NOx. ER blockade with ICI182,780 prevented NEB-induced NOx excretion in OVX rats. In the aortae of SO females, NEB treatment did not alter eNOS expression. In OVX rats eNOS expression was increased two-fold after NEB application and this could be prevented by pretreatment with ICI182,780. In contrast to eNOS, NEB did not influence caveolin-1 expression in either group. - Conclusion: The ability of NEB to up-regulate NOx excretion in male and OVX SHR and the inhibitory effect of ICI182,780 on NEB-induced NOx excretion suggests that NEB has an estradiol-agonistic action in vivo. NEB provokes NO generation by up-regulation of eNOS protein expression, whereas the expression of the negative eNOS regulator caveolin-1 remains unaffected.
Gesehen am 07.04.2022